PRODUKTIVITAS PADA PROYEK KONSTRUKSI - Taufik Dwi Laksono (Teodolita ( Media Komunikasi Ilmiah di Bidang Teknik ), 2007)
AbstractÂ Lact in the Indonesia eployment awareness concerning the importance of productivity, is one of the causal factors of the job lack produced, therefore, an understanding about productivity is highly important in a job world, no exception in a construction project. Productivity on the construction project is a comparison between the projects outputs producted, with the input given in a serial project activities. There are a lot of factors influence this productivity on the construction project are including kinds of job, resources, work environmental condition, contract requirements and working methods. Among the five factors, the resources factor in this matter is labour resources have a high role in a productivity measurementÂ Keywords : Productivity, Construction, Project